2018
DOI: 10.3389/fmicb.2018.01657
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Genome Sequence-Driven Characterization of tal Effector Gene Repertoires Reveals Novel Variants With Altered Specificities in Closely Related Malian Xanthomonas oryzae pv. oryzae Strains

Abstract: Rice bacterial leaf blight (BLB) is caused by Xanthomonas oryzae pv. oryzae (Xoo) which injects Transcription Activator-Like Effectors (TALEs) into the host cell to modulate the expression of target disease susceptibility genes. Xoo major-virulence TALEs universally target susceptibility genes of the SWEET sugar transporter family. TALE-unresponsive alleles of OsSWEET genes have been identified in the rice germplasm or created by genome editing and confer resistance to BLB. In recent years, BLB has become one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…Although all five of the known clade III SWEET genes in rice can function as susceptibility genes for bacterial blight, only three are known to be targeted in nature 10 . More specifically, SWEET11 expression is induced by strains encoding the TALe PthXo1, SWEET13 by PthXo2 and SWEET14 by any one of several TALes, namely AvrXa7, PthXo3, TalC and TalF (originally Tal5) 7,915 (Table 1). Effectors of Xoo that target clade III SWEET genes are referred to as major TALes owing to their strong virulence effect.…”
Section: Mainmentioning
confidence: 99%
“…Although all five of the known clade III SWEET genes in rice can function as susceptibility genes for bacterial blight, only three are known to be targeted in nature 10 . More specifically, SWEET11 expression is induced by strains encoding the TALe PthXo1, SWEET13 by PthXo2 and SWEET14 by any one of several TALes, namely AvrXa7, PthXo3, TalC and TalF (originally Tal5) 7,915 (Table 1). Effectors of Xoo that target clade III SWEET genes are referred to as major TALes owing to their strong virulence effect.…”
Section: Mainmentioning
confidence: 99%
“…Some individual Xoo strains have evolved a set of distinct TALE effectors that collectively target several members of the clade III SWEET family. The presence of these redundant TALEs thereby trumps single “loss-of-tale-responsiveness” resistance alleles [ 11 , 12 , 17 , 47 ]. For example, Kitaake lines carrying TALEN-induced mutation in the SWEET14 promoter [ 13 , 15 ] exhibit resistance to strains which depend exclusively on matching AvrXa7/PthXo3 for clade III SWEET family induction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Xa41(t) (having 18 bp deletion) offers broad-spectrum resistance against a large collection of Xoo strains (Hutin et al, 2015b). Recently it was reported that some Xoo strains still cause infection in rice despite R genes (Carpenter et al, 2018;Doucouré et al, 2018). These failures have prompted plant genome engineers to develop resistance against this rapidly evolving pathogen by mutating susceptibility genes.…”
Section: Discussionmentioning
confidence: 99%